Psychobiological stress regulation through group music therapy in depressive women: results from the randomized-controlled music therapy for depression (MUSED-) study - Gäbel, Christine; Jarczok, Marc N.; Aguilar-Raab, Corina; Rittner, Sabine; Warth, Marco; Stoffel, Martin; Ditzen, Beate (Universität, 2025)
Abstract Background. Major Depressive Disorder (MDD) is known as a stress-related disease which affects women more often than men. Music therapy (MT) has been shown to be effective in the treatment of MDD. However, clinical trials investigating the effects of MT on psychological and psychobiological stress-related outcomes in women suffering from MDD are still scarce. Methods. This study was conducted as a randomized controlled trial, with participants assigned to either an intervention group (IG), which received group MT (GMT), or a waitlist control group (CG) which received GMT 6 months later. The primary objective was to assess the impact of GMT on psychological stress outcomes (chronic stress, stress coping, and stress experienced in daily life) and psychobiological stress markers (diurnal salivary cortisol levels and circadian heart rate variability), considering the effects of both group allocation and time. Outcome measurements were taken before, immediately after, and for some variables, 10 weeks following the intervention period. Results. A total of 102 women between 18 and 65 years diagnosed with current MDD took part in the study. Overall, the IG demonstrated more substantial stress-reducing effects compared to the CG. Significant improvements were observed in general stress coping, positive thinking, daily life stress, and cortisol. Conclusion. GMT is a cost-effective and non-invasive approach to effectively address the stress-related psychological and psychobiological burden associated with MDD. To demonstrate long-term effects and gain a better understanding of the underlying mechanisms, further methodologically robust studies are needed.
Gesehen am 12.02.2025
Keywords: Forschungsdaten; Datenbank